Pengujian Peraturan Perundang-Undangan Di Indonesia: Persoalan Dan Jalan Keluarnya - Hajri, Wira Atma; Rahdiansyah, Rahdiansyah (UIR Press, 2018)
The existence of two institutions that review of legislation in Indonesia resulted in various problems especially in terms of legal certainty, institutional authority, and legal vacuum. In terms of legal certainty, which decisions to follow, the decision of the Supreme Court or the decision of the Constitutional Court. When the Constitutional Court tests the law, while the Supreme Court examines under the law, it does not mean that the Constitutional Court is higher than the Supreme Court. In terms of authority, the neglect of the Supreme Court ruling as has been done by the General Election Commission, of course, disturbs the authority of the Supreme Court. How is the decision of the institution of the Supreme Court not run by the Election Commission. The issue is due to a Constitutional Court ruling which provides a different interpretation of the law as a test case by the Supreme Court, that is another matter. In terms of legal vacuum, suppose the absence of a judicial institution authorized to test the Decree of the People's Consultative Assembly.